2016
DOI: 10.11609/jott.2599.8.14.9619-9629
|View full text |Cite
|
Sign up to set email alerts
|

Cnemaspis flaviventralis, a new species of gecko (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India

Abstract: Cnemaspis flaviventralis, a new species of day gecko, is described from the forests of Amboli, Sindhudurg District, Maharashtra State, northern Western Ghats, India.  The new species was previously confused with the sympatric species Cnemaspis girii, C. indraneildasii, C. kolhapurensis and C. goaensis.  It is distinguished from C. giri by having spine-like tubercles on flanks, granular dorsal scales intermixed with large, depressed, slightly keeled scales (vs. lack of spine-like tubercles on flanks, granular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In total, 240 Cnemaspis individuals were examined for morphological analyses, including type specimens of the new lineages described herein as well as extant species from Peninsular India, topotypical specimens, type specimens, and other museum specimens listed in the material examined section (Appendix II). Comparative data on the described Cnemaspis species from Peninsular India were also taken from published literature ( Agarwal et al, 2020b ; Cyriac & Umesh, 2013 , 2014 ; Cyriac et al, 2018 , 2019 , 2020 ; Das & Bauer, 2000 ; Giri et al, 2009a , 2009b ; Khandekar, 2019 ; Khandekar et al, 2019a , 2019b , 2020b ; Manamendra-Arachchi et al, 2007 ; Mirza et al, 2014 ; Mukherjee et al, 2005 ; Murthy et al, 2019 ; Sayyed et al, 2016 , 2018 , 2019 , 2020 ; Srinivasulu et al, 2015 ). Counts and external observations of morphology and meristic characters were made under a Leica stereo dissecting microscope, and on the left side of the body for symmetrical characters where possible.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 240 Cnemaspis individuals were examined for morphological analyses, including type specimens of the new lineages described herein as well as extant species from Peninsular India, topotypical specimens, type specimens, and other museum specimens listed in the material examined section (Appendix II). Comparative data on the described Cnemaspis species from Peninsular India were also taken from published literature ( Agarwal et al, 2020b ; Cyriac & Umesh, 2013 , 2014 ; Cyriac et al, 2018 , 2019 , 2020 ; Das & Bauer, 2000 ; Giri et al, 2009a , 2009b ; Khandekar, 2019 ; Khandekar et al, 2019a , 2019b , 2020b ; Manamendra-Arachchi et al, 2007 ; Mirza et al, 2014 ; Mukherjee et al, 2005 ; Murthy et al, 2019 ; Sayyed et al, 2016 , 2018 , 2019 , 2020 ; Srinivasulu et al, 2015 ). Counts and external observations of morphology and meristic characters were made under a Leica stereo dissecting microscope, and on the left side of the body for symmetrical characters where possible.…”
Section: Methodsmentioning
confidence: 99%
“…Based on four males and four females, Sayyed et al (2016) described Cnemaspis flaviventralis (Fig. 1) from the Amboli (15.9600°N.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Although, the northern WG is thought to be depauperate compared to the southern WG (Gunawardene et al 2007), ongoing taxonomic research are continuously adding new species of reptiles and amphibians to the endemic diversity of this region (e.g. Sharma 1976;Padhye et al 2013;Mirza et al 2014;Deepak et al 2016;Sayyed et al 2016;Giri et al 2019a, b;Khandekar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Cnemaspis Strauch, 1887 is one of the most diverse clades of geckos in India and recent studies have indicated that the diversity documented within this clade is far from complete (Khandekar 2019;Agarwal et al 2020;Cyriac et al 2020). The diversity of Cnemaspis is also exceptionally high in the NWG and recent studies have been describing several new species from the region (Sayyed et al 2016(Sayyed et al , 2018Khandekar et al 2019;Sayyed and Sulakhe 2020). Currently 11 species of Cnemaspis are known from NWG of Maharashtra which fall into three separate clades -wynadensis clade, goaensis clade and giri clade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation